Comparative Effectiveness of Antibiotic Class Strategies in the Management of Sepsis in India: Evidence from Real-World Clinical Data - Gupta , Anil Kumar; Singh, Rakesh Kumar; Sharma, Priya (Journal of Society Medicine, 2026)
Introduction: Sepsis remains a major cause of morbidity and mortality in intensive care units worldwide, particularly in low-and middle-income countries, where antimicrobial resistance is highly prevalent. In India, gram-negative pathogens dominate bloodstream infections and are frequently associated with high levels of carbapenem resistance, creating significant challenges in selecting appropriate empiric antibiotic therapy. However, comparative evidence regarding antibiotic class strategies in the Indian sepsis setting remains limited. Therefore, this study aimed to evaluate the comparative effectiveness of major antibiotic class strategies used in the management of sepsis in India using real-world clinical and surveillance data. Methods: A secondary analysis of publicly available real-world datasets was conducted. Evidence was synthesized from the multicenter SEPSIS INDIA prospective registry, national antimicrobial resistance surveillance data from the Indian Council of Medical Research (ICMR), and published Indian real-world cohorts evaluating novel β-lactam/β-lactamase inhibitor therapies. Data regarding empiric antibiotic exposure patterns, pathogen distribution, antimicrobial resistance profiles, clinical outcomes, and healthcare utilization were systematically analyzed to compare antibiotic class strategies used in sepsis management. Results: Approximately half of the ICU patients with sepsis had positive blood cultures, with gram-negative organisms accounting for nearly 80% of the isolates. Carbapenem-resistant pathogens were detected in approximately 57% of culture-positive cases. Empiric therapy was predominantly carbapenem-based, particularly meropenem (≈55%), followed by β-lactam/β-lactamase inhibitor regimens, such as piperacillin–tazobactam (≈22%). Polymyxins and glycopeptides were frequently used as adjunctive agents. Mortality was higher among infections caused by carbapenem-resistant organisms than among those caused by carbapenem-susceptible pathogens. Real-world cohorts evaluating ceftazidime–avibactam demonstrated encouraging microbiological success rates and acceptable clinical outcomes in infections caused by carbapenem-resistant gram-negative bacteria. Conclusion: Real-world evidence indicates that antimicrobial resistance substantially influences antibiotic effectiveness in the management of sepsis in Indian ICU patients. Optimizing empiric therapy through local antibiogram-guided strategies, antimicrobial stewardship, and rapid diagnostic integration is essential to improve outcomes and mitigate the growing impact of multidrug-resistant infections.